2023
DOI: 10.21203/rs.3.rs-2410967/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On The Peer Review Reports: Does Size Matter?

Abstract: Scientometers and sociologists of science have spilled much ink on the topic of peer review over the past twenty years given its primordial role in a context marked by the exponential growth of scientific production and the proliferation of predatory journals. Although the topic is addressed under different prisms, few studies have empirically analyzed to what extent it can affect the quality of publications. Here we study (1) the link between the length of reviewers' reports and the citations received by publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…13,14 This premise is supported by research by Yadav, 15 who found that review volume was positively associated with overall review quality. Additionally, a recent study 16 found that lengthier reviews were positively associated with the number of citations received by the article (arguably a measure of article quality). Thus, under the assumption that a very low word count reflects, at least to some degree, the quality of a peer review, this study aimed to determine the prevalence of very short peer reviews in 3 leading general medical journals: The BMJ, PLOS Medicine, and BMC Medicine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 This premise is supported by research by Yadav, 15 who found that review volume was positively associated with overall review quality. Additionally, a recent study 16 found that lengthier reviews were positively associated with the number of citations received by the article (arguably a measure of article quality). Thus, under the assumption that a very low word count reflects, at least to some degree, the quality of a peer review, this study aimed to determine the prevalence of very short peer reviews in 3 leading general medical journals: The BMJ, PLOS Medicine, and BMC Medicine.…”
Section: Introductionmentioning
confidence: 99%
“…This premise is supported by research by Yadav, who found that review volume was positively associated with overall review quality. Additionally, a recent study found that lengthier reviews were positively associated with the number of citations received by the article (arguably a measure of article quality).…”
Section: Introductionmentioning
confidence: 99%